(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Accurate assessment of recovery following general anaesthesia is essential for safe and timely discharge from the post-anaesthesia care unit (PACU). The Modified Aldrete Score (MAS) and Fast-Track Criteria (FTC) are widely used tools, but their comparative effectiveness in laparoscopic surgery remains uncertain. Aim: To compare the Modified Aldrete Score and Fast-Track Criteria in assessing recovery and determining discharge readiness following general anaesthesia in patients undergoing laparoscopic surgery. Methods: In this prospective observational study, 200 patients (ASA I–II) aged 18–65 years undergoing elective laparoscopic surgery under general anaesthesia were evaluated. Recovery was assessed using MAS and FTC at 5 minutes, 30 minutes, 2, 6, 12, and 24 hours post-extubation. Time to achieve discharge readiness (MAS ≥9, FTC ≥12), Visual Analogue Scale (VAS) scores, and agreement between the tools were analysed. Results: At 5 minutes, 47.5% (MAS) and 46% (FTC) of patients were eligible for transfer, increasing to 94.5% and 90.5% at 30 minutes, and 100% in both groups by 2 hours. Mean time to discharge readiness was significantly shorter with MAS (23.1 ± 26.4 minutes) compared to FTC (27.1 ± 32.5 minutes; p = 0.002). Agreement between MAS and FTC was almost perfect at 5 minutes (kappa = 0.97) and substantial at 30 minutes (kappa = 0.71). MAS scores improved from 8.3 ± 0.6 at 5 minutes to 10 at 12 hours, while FTC scores increased from 11.3 ± 0.7 to 13.9 ± 0.1 over the same period. VAS scores decreased significantly from 6.2 ± 0.5 at 5 minutes to 1.2 ± 0.4 at 24 hours (p < 0.001). Antiemetics were required in 21.5% of patients, while all patients required rescue analgesia. Conclusion: The Modified Aldrete Score enables earlier identification of discharge readiness, whereas Fast-Track Criteria provides a more comprehensive assessment by incorporating pain and postoperative nausea and vomiting. A combined or context-based approach may optimize postoperative recovery assessment and PACU discharge decisions.